PI SLIDING MODE CONTROL FOR MISMATCHED UNCERTAIN SYSTEMS - Ab Ghani, Mohd Ruddin (Penerbit UTM, 2002)
This paper focused on the proportional-integral sliding mode control for uncertain dynamic systems with mismatch uncertainties. First, the switching surface condition for the sliding mode control is synthesized. Then the control law is designed to drive the state trajectories of the system onto the sliding surface and the system remains in it thereafter. The proposed control law is applied to a numerical example and its performance is compared to the state variable feedback control system design methodology.